The analysis of macroeconomic development of the United Kingdom from 2000 to 2018 - Zeman, Mikuláš (2019)
The master’s thesis analyzes strengths, weaknesses, opportunities and threats of the UK’s economy from 2000 to 2018. The method of research is the comparison with the average of OECD and Eurozone members. Results of the analysis are stated in SWOT matrix. The master’s thesis also evaluates economic consequences of the Brexit referendum. The analysis shows that the referendum had no important impact on the UK’s macroeconomic fundamentals. The thesis predicts future impacts of Brexit as well. The UK will remain a strong international economy despite its withdrawal from the EU.